Autobiography and Cankar’s novel New life - Zupan Sosič, Alojzija (Slavia Centralis, 2022)
In the discussion, Cankar’s modern understanding of autobiography offered the possibility of explanation with the help of the concept of experientiality. In Cankar’s narrative works, including the novel New Life (1908), the question of objectivity and subjectivity comes into contact with the share of autobiography in an innovative way – the author, narrator or character no longer asks the classic positivist question about the verifiability of biographical data, but emphasises the importance of experientiality, which became the starting point in connection with the narrative only later, in so-called natural narratology by Monika Fludernik. In Cankar’s narratives, including in the novel New Life, the experientiality is equated with frankness, which acts as a provocation in places due to the fake position of testimony or confession. In addition to experientiality, frankness and provocativeness, the novel in question also has self-reflexivity, which is outlined by the auto-thematic nature and the similar profile of the main character, that is, Anton Grivar.